Expected willingness to pay for wind energy in Atlantic Canada. (June 2019) - Koto, Prosper Senyo; Yiridoe, Emmanuel K.
Abstract: We investigate the demand-side of wind energy in three provinces in Atlantic Canada, including New Brunswick, Nova Scotia and Prince Edward Island. Empirical questions addressed include: (i) What are the determinants of the probability of paying a non-zero premium for electricity generated using wind technology?; (ii) Given participation, what drives how much more households are willing to pay a month, and what is the monthly premium or expected willingness-to-pay (WTP)?; and (iii) Is there heterogeneity in the expected WTP? The study design follows the contingent valuation framework and the survey questionnaire follows a payment-scale format, reducing the starting point bias and reduces the incidence of item non-response. The data is from a stratified random sample. We employ two-stage models, Cragg's hurdle and the two-part econometric models in the analysis. Scope and 0 WTP effects are explicitly explored. We find that the overall probability of participation is 0.73. University education, income, residential property ownership, concerns about the presence of wind turbines in neighborhoods, and externality affect the likelihood of participation. Households are willing to pay 14% more per month in energy bill for wind power. There is evidence of scope sensitivity. The results provide insights on what proportion of the population will participate and how much more they are willing to pay for wind energy. Highlights: We calculated the conditional mean premium willingness-to-pay (WTP) for wind energy. Estimated average marginal effects for the intensive and extensive margins of WTP for wind energy. Probability of participation is 0.73, and increases to 0.83 with the exclusion of protest 0 WTP. Respondents are willing to pay 14% more monthly for wind energy in Atlantic Canada.